EFFECT OF EXTREMELY HIGH FREQUENCY ELECTROMAGNETIC IRRADIATION TREATMENT ON GERMINATION, GROWTH AND AMYLASE ACTIVITY OF WHEAT SEEDS (Proceedings of the YSU B: Chemical and Biological Sciences, 2023)
In this work, the effect of low-intensity (non-thermal, flux capacity 0.06 mW/cm2) electromagnetic irradiation (EMI) of extremely high frequency (EHF) (42.2 GHz and 50.3 GHz) as pre-sowing treatment on germination, early growth and α-amylase activity of wheat seeds (Triticum aestivum L.) has been studied. The measurements conducted during seed germination were the germination energy and germination power, germination index, shoot and root length, as well as fresh weight. The laboratory experiment followed a completely randomized design, with four treatments (control, 5 min – T5, 10 min – T10, and 15 min – T15) and three replications. It was shown that EHF EMI pre-sowing treatment at both used frequencies favored the germination and growth of wheat seeds, and results were more expressed at a frequency of 50.3 GHz – the resonant frequency of water. We found that EMI with 50.3 GHz for 10 min significantly improved germination energy (by 6.5%) and germination power (by 7.6%). At the same time, shoot high (by 11%), root length (by 12%) and fresh weight (15%) were enhanced significantly at seedling stage compared with the control. Furthermore, the measured activity of α-amylase reviled that EMI-treatment increased the enzyme activity more than 2-fold, thereby probably promoting wheat germination.
Keywords: electromagnetic irradiation of extremely high frequency; wheat treatment; seed germination; seedling growth; α-amylase activity